To have or to be ? - "Fromm, Erich" (London, 1976)
To Have Or to Be? is one of the seminal books of the second half of the 20th century. Nothing less than a manifesto for a new social and psychological revolution to save our threatened planet, this book is a summary of the penetrating thought of Eric Fromm. His thesis is that two modes of existence struggle for the spirit of humankind: the having mode, which concentrates on material possessions, power, and aggression, and is the basis of the universal evils of greed, envy, and violence; and the being mode, which is based on love, the pleasure of sharing, and in productive activity. To Have Or to Be? is a brilliant program for socioeconomic change.
Keywords: Sociology